The Role Of Religious Coping Towards Stress In Adolescents At Islamic Boarding Schools - Kartika Alundari; Rr Amanda Pasca Rini (AGUSPATI Research Institute, 2023)
The purpose of this study was to examine the effect of koping religius on the stress experienced by adolescents in Suryalaya Islamic boarding schools. This study is a quantitative study using simple regression data analysis on 180 respondents aged 16-17 years. Data was collected by distributing questionnaires using a questionnaire with a total of 32 items for the stress variable and 30 items for koping religius that was proven to be accurate and trustworthy after being put to the test. The results showed that there was an influence of koping religius on stress showing a number of .601 or 60.1%, which means that the variable koping religius had an effect on stress in adolescents as much as 60.1% while 39.9% was due to other variables not mentioned in this study.